The (re)creation of the myth of Mithras - Jaime (Antiguo Oriente, 2021)
The (Re)creation of the Myth of Mithras In absence of oriental or classical texts referring to a myth related to the god Mithras, scholars are divided in the interpretation of the iconography of the cult in Roman period. Since the pioneer studies of the Belgian scholar Franz Cumont, the dominant interpretation was that the illustrated panels and the tauroctony, bull’s sacrifice by Mithras, were the narratological icons of Mithras’ story. Another research stream, especially dynamic in the last decades of 20th Century, interpreted the scene of Mithras killing the bull as a stellar map, all the iconic elements being constellations or figures related to the planetary world. No less sophisticated is the newest proposal that identifies all the main scenes (Mithras’ birth from the rock, Mithras carrying the bull -transitus-, the water miracle, the tauroctony, or even his apotheosis) not as sequences of a narrative, but illustrations of a unique demiurgic act: the creation of the world, the beginning of life. My argument in this paper is that from the perspective of the Roman viewer it is very unacceptable to deny the narratological character of at least of part of the iconography, and thereafter it is necessary to assume the existence of a divine story recognisable by the cultores, even if local iconic preferences underlined parts of the story or its symbolic meanings.